Increase in Community Interest in Making Aloe Vera-Based Hand Sanitizer: Peningkatan Minat Masyarakat dalam Pembuatan Hand Sanitizer Berbahan Lidah Buaya (Indonesian Journal of Cultural and Community Development, 2024)
The general background hand hygiene is crucial in preventing the spread of diseases, as hands are the primary pathway for microorganisms to enter the body. Specific background although alcohol-based hand sanitizers are widely used, they can cause skin dryness, prompting the need for alternatives made from natural ingredients. Aloe vera is a readily available plant with moisturizing properties that can serve as an alternative ingredient. Knowledge gap however, community knowledge regarding the production of aloe vera-based hand sanitizers remains limited. Aims this community service project aimed to educate participants on the process of making natural hand sanitizers using aloe vera through workshops and demonstrations. Results after the training, 60% of participants expressed interest in making their own hand sanitizers, citing easy access to materials, productive use of free time, and business opportunities as their motivations. Novelty the use of aloe vera as a base for hand sanitizer offers a skin-friendly and sustainable alternative to alcohol-based products. Implications this program not only raised awareness about hand hygiene but also empowered the community by introducing a simple, cost-effective method to create hand sanitizers, potentially opening new avenues for small-scale businesses.Highlights: • Aloe vera-based hand sanitizers offer a natural alternative to alcohol-based products.• 60% of participants expressed interest in making hand sanitizers after the training.• The program opens business opportunities by utilizing easily accessible materials.Keywords: Hand Sanitizer, Aloe Vera, Community Training, Natural Ingredients, Small-Scale Business